PENGARUH PERBEDAAN DURASI APLIKASI KONDISIONER TERHADAP GAMBARAN PENETRASI SEMEN IONOMER KACA PADA DENTIN SULUNG (Evaluasi Scanning Electron Microscopy) - Suzanty Ariany; Ismu Suharsono Suwelo; Heriandi Sutadi (Faculty of Dentistry, Universitas Indonesia, 2015)
The purpose of this study was to determine whether different durations of conditioner application influenced glass ionomer cement penetration in dentin primary teeth. The conditioner being used was 10% polyacrylic acid. Samples in this study were 40 non-carious primary mandibular incisors. Samples were divided into 4 groups (10 samples each): group A, withoud conditioner, group B, with 10 seconds of conditioner application, group C, with 20 seconds of conditioner application, and group D with 30 seconds of conditioner application. Penetration of glass ionomer cement was observed using scanning electron microscopy (SEM) with 200x magnification. One-way ANOVA and Tukey HSD test showed significant difference between groups. Longer conditioner application resulted in longer glass ionomer penetration in dentin of primary teeth.